Synthesis of ureasil-polyether film forming materials by using environmentally friendly solvent - Juliana Fernandes Mendes; João Augusto Oshiro Junior; Camila Garcia da Silva; Leila Aparecida Chiavacci (São Paulo State University (UNESP), 2021)
Organic inorganic hybrids present several advantages as drug release systems, such as: high flexibility, high mechanical and thermal resistance, transparency, and low water solubility. These hybrids are synthesized through a chemical route named sol-gel that usually uses as solvente tetrahydrofuran (THF). Objetives: To develop film formers from hybrid materials replacing THF with ethanol, a less toxic solvent for skin application and for the environment. Methods: Four polymers were used: two based on polyethylene oxide (PEO) with molecular weight of 500 and 1900 g mol-1 and two based on polypropylene oxide (PPO), with molecular weight of 400 and 2000 g mol-1. The structural analysis was performed by FTIR, 1H-NMR and 29Si-NMR, and the thermal-mechanical analysis by DSC and TG-DTA. Results: The results of the thermo-mechanical analysis revealed that the solvent replacement did not affect the thermal stability and flexibility of the di-ureasil hybrid. Conclusions: Structural characterization confirmed the formation of hybrids both in THF and in ethanol. Therefore, ethanol is an excellent solvent for the synthesis of these hybrid matrices, since it allows obtaining the same material without changing its characteristics, with some advantages, however, over THF. Furthermore, this paper describes the efficiency of ethanol as a solvent, which is environmentally friendly, to replace THF in the physical-chemical characteristics of these filming former materials.